x(x-6)+8=0

Apply the distributive property.

x⋅x+x⋅-6+8=0

Multiply x by x.

x2+x⋅-6+8=0

Move -6 to the left of x.

x2-6x+8=0

x2-6x+8=0

Consider the form x2+bx+c. Find a pair of integers whose product is c and whose sum is b. In this case, whose product is 8 and whose sum is -6.

-4,-2

Write the factored form using these integers.

(x-4)(x-2)=0

(x-4)(x-2)=0

If any individual factor on the left side of the equation is equal to 0, the entire expression will be equal to 0.

x-4=0

x-2=0

Set the first factor equal to 0.

x-4=0

Add 4 to both sides of the equation.

x=4

x=4

Set the next factor equal to 0.

x-2=0

Add 2 to both sides of the equation.

x=2

x=2

The final solution is all the values that make (x-4)(x-2)=0 true.

x=4,2

Solve Using the Square Root Property x(x-6)+8=0